1994
DOI: 10.1111/j.1432-1033.1994.tb18578.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of tissue‐type plasminogen activator binding sites on fibrin using distinct fragments of fibrinogen

Abstract: It is well established that tissue-type plasminogen activator (t-PA) binds to the D region of fibrin(ogen) and that two distinct CNBr fragments of fibrinogen (FCB), FCB-2 and FCB-5, comprising parts of this region, stimulate plasminogen activation by t-PA. In the present work, ligandbinding studies were performed to characterize the interactions between t-PA and the corresponding fibrin regions using a well defined model of a fibrin surface and both FCB-2 and FCB-5 in liquid and solid phase. Binding isotherms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…sctPA is secreted as an active enzyme and is further strongly activated by specific interactions, primarily through its second kringle domain, with a wide variety of extracellular matrix components including fibrin(ogen) (19,20), laminin (21), fibronectin (22), and lysinerich molecules as shown here. Because sctPA activated by poly-D-lysine or fibrinogen͞gelatin is inhibited by rMaspin(i), it is likely that the second kringle domain of sctPA plays a critical role in the fine modulation of its activity by both stimulators and inhibitors.…”
Section: Discussionmentioning
confidence: 83%
“…sctPA is secreted as an active enzyme and is further strongly activated by specific interactions, primarily through its second kringle domain, with a wide variety of extracellular matrix components including fibrin(ogen) (19,20), laminin (21), fibronectin (22), and lysinerich molecules as shown here. Because sctPA activated by poly-D-lysine or fibrinogen͞gelatin is inhibited by rMaspin(i), it is likely that the second kringle domain of sctPA plays a critical role in the fine modulation of its activity by both stimulators and inhibitors.…”
Section: Discussionmentioning
confidence: 83%
“…The binding of tPA to Fb is mediated by the finger-like and kringle 2 domains [4]. It has been suggested that these domains are involved in two different types of binding: lysin-dependent (kringle 2 and Ddomain of Fb) and lysin-independent (finger-like domain and D-domain of Fb) [29]. The latter domains contribute to a greater extent to the total binding which becomes highly affinity due to cooperative binding of tPA by the two abovementioned low-affinity centres and accelerates Pmg activation [30].…”
Section: Plasminogen Activators and Their Interaction With Fibrinmentioning
confidence: 99%
“…The finger domain and the Kringle-2 domain serve as the primary fibrin binding sites [86]. The Kringle-2 domain plays a role in C-terminal lysine binding, while the finger domain can bind to a region in the fibrin γ -nodule in a lysine-independent mechanism [91] or to amyloid-like cross-beta structures [44], which have been hypothesized to form in fibrin α -polymers [14, 92]. Recent work has shown that the tPA finger domain plays the predominant role in binding to fibrin during fibrinolysis [93, 94], even in proteolytically degraded fibrin.…”
Section: Fibrinolytic Agents: Activation and Inhibitionmentioning
confidence: 99%